2018
DOI: 10.1371/journal.pone.0198646
|View full text |Cite
|
Sign up to set email alerts
|

Thought probes during prospective memory encoding: Evidence for perfunctory processes

Abstract: For nearly 50 years, psychologists have studied prospective memory, or the ability to execute delayed intentions. Yet, there remains a gap in understanding as to whether initial encoding of the intention must be elaborative and strategic, or whether some components of successful encoding can occur in a perfunctory, transient manner. In eight studies (N = 680), we instructed participants to remember to press the Q key if they saw words representing fruits (cue) during an ongoing lexical decision task. They then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 90 publications
1
28
2
Order By: Relevance
“…The need for engaging in such constructive and slow, effortful processes (depicted as “Deliberate Future Thinking 1” in Figure 2) may occur in more complex situations involving competing demands, motivational conflicts, or when planning a sequence of actions to achieve a superordinate goal (e.g., steps involved in planning a trip to a foreign country; see Kvavilashvili & Ellis, 1996). The main point of the model is that, although humans have the ability to engage in such constructive episodic future thinking processes (as demonstrated by numerous studies on deliberate episodic future thinking), the majority of everyday situations allow them to circumvent this initial stage and form their intentions quickly and without too much expenditure of effort and executive resources (e.g., see Scullin et al, 2018). Therefore, such decisions about the future can often occur “on the go” while being engaged in other activities such as driving, jogging, or doing washing up (Anderson & McDaniel, 2019).…”
Section: Toward An Integrative View On Prospective Thought: the Pragmmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for engaging in such constructive and slow, effortful processes (depicted as “Deliberate Future Thinking 1” in Figure 2) may occur in more complex situations involving competing demands, motivational conflicts, or when planning a sequence of actions to achieve a superordinate goal (e.g., steps involved in planning a trip to a foreign country; see Kvavilashvili & Ellis, 1996). The main point of the model is that, although humans have the ability to engage in such constructive episodic future thinking processes (as demonstrated by numerous studies on deliberate episodic future thinking), the majority of everyday situations allow them to circumvent this initial stage and form their intentions quickly and without too much expenditure of effort and executive resources (e.g., see Scullin et al, 2018). Therefore, such decisions about the future can often occur “on the go” while being engaged in other activities such as driving, jogging, or doing washing up (Anderson & McDaniel, 2019).…”
Section: Toward An Integrative View On Prospective Thought: the Pragmmentioning
confidence: 99%
“…In summary, the proposed pragmatic dual process model may provide a useful initial framework for studying the nature and mechanisms of everyday prospection. This model and the review of relevant studies indicate that the progress in the study of naturally occurring prospective thought can only be achieved by more collaborative approach, and by adopting methods across different research fields to creatively address new research questions, which can result in novel findings and further increase our understanding of everyday prospection (e.g., Rummel et al, 2017; Scullin et al, 2018; Seli, Smilek, et al, 2018).…”
Section: Toward An Integrative View On Prospective Thought: the Pragmmentioning
confidence: 99%
“…However, the correspondence may not be perfect. For example, in categorical conditions participants may generate exemplars (Scullin et al, 2018), effectively turning nonfocal into focal tasks. Therefore, we use the theoretically neutral terms 'single-item' and 'category' here.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that "the conscious formation of an intention may not always be necessary for successful remembering as stipulated in the prospective memory literature" (p. 873). More recently, Scullin et al (2018) probed the thoughts of 680 participants during the encoding of PM intentions in 8 experiments and found that participants frequently reported mind wandering, "hardly thinking about the PM task", or engaging in idiosyncratic, "perfunctory" processes rather than following the experimenter's explicit instructions. The authors summarized their results by concluding that participants often encode PM intentions with little effort, that variability in encoding effort often has little effect on PM remembering, and that PM intentions are often encoded "in passing".…”
Section: Discussionmentioning
confidence: 99%